Muslim aspirations in Bangladesh: looking back and redrawing boundaries - Huq, Samia (© 2014 Oxford University Press, 2016)
This article was published in Being Muslim in South Asia: Diversity and Daily Life [© 2014 Oxford University Press] and the definite version is available at http://www.oxfordscholarship.com/view/10.1093/acprof:oso/9780198092063.001.0001/acprof-9780198092063-chapter-12 The article website is at: https://global.oup.com/academic/product/being-muslim-in-south-asia-9780198092063?cc=bd&lang=en&